2014
DOI: 10.1002/erv.2326
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Remediation in Anorexia Nervosa and Related Conditions: A Systematic Review

Abstract: Research evidence for cognitive remediation therapy's (CRT) effectiveness for anorexia nervosa (AN) has been gathering. This approach is also increasingly being implemented in other disorders including major depressive disorder, obsessive-compulsive disorder and autistic spectrum disorder that share commonalities with AN in neuropsychological profiles and clinical presentations. This systematic literature review identified and appraised the current evidence base to see whether evidence from related conditions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
132
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 157 publications
(151 citation statements)
references
References 76 publications
9
132
0
3
Order By: Relevance
“…Furthermore, as normative body image and eating difficulties have per se important negative biopsychosocial consequences (e.g., [7]), the current study offers important directions for the development of preventive programmes focused on body image and eating behaviours directed at adolescent girls. In fact, this study seems to support the relevance of therapeutic approaches that target cognitive rigidity and promote flexibility [49,50]. In particular, the development of higher psychological flexibility may be beneficial to attenuate the impact of body and weight dimensions on eating difficulties, and to help adolescent girls to focus on and engage with valued life domains [51,33].…”
Section: It Is Increasingly Recognized That Adolescence Is a Criticalmentioning
confidence: 56%
“…Furthermore, as normative body image and eating difficulties have per se important negative biopsychosocial consequences (e.g., [7]), the current study offers important directions for the development of preventive programmes focused on body image and eating behaviours directed at adolescent girls. In fact, this study seems to support the relevance of therapeutic approaches that target cognitive rigidity and promote flexibility [49,50]. In particular, the development of higher psychological flexibility may be beneficial to attenuate the impact of body and weight dimensions on eating difficulties, and to help adolescent girls to focus on and engage with valued life domains [51,33].…”
Section: It Is Increasingly Recognized That Adolescence Is a Criticalmentioning
confidence: 56%
“…Cognitive therapies that directly target deficits associated with autistic traits such as socio-emotional deficits and problems with attention switching, may be particularly effective in this population. Previous work has found that cognitive remediation therapy (CRT, Tchanturia et al, 2014) and emotion skills training (CREST, was helpful for ED patients, which could be extended to individuals at risk for both autistic traits and eating pathology. Finally, as difficulties regulating emotions are associated with the development of a range of psychopathologies including EDs and ASD (Globerson et al, 2015), interventions targeting emotion regulation may provide a transdiagnostic approach to resilience and mental health promotion programs, and the prevention of psychopathology more broadly.…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive training has been found to hold promises for personalized care of individuals in numerous mental illnesses, as well as been a target in the development of behavioural interventions [6]. A key clinical intervention targeting thinking styles, with growing empirical support, is cognitive remediation therapy (CRT; for review see [7]). CRT is an easy to deliver, manualised treatment, tailored to target problematic thinking styles (for details of the manual see http://www.katetchanturia.com-publications; for current research evidence see [8]).…”
Section: Introductionmentioning
confidence: 99%